Bot contracts (B.O.T) and its applications in Algeria. - Boumezber, Badis (Journal of Human Sciences, 2021)
When our study of the law Number :  08/14 of July, 20th ,2008 amanded and supplementing  Law Number: 90/30 containing the national property law, we observed that the most important statement in this amendment that added a new kind of concession contracts did not know the Algerian legal system than before, After the text of the concession contracts involving the exploitation of public property or finance or exploit public enterprise, touched on the possibility of building a facility back at the end of duration the concession to the awarding authority. Accordingly, we note that the national average property law included a new kind of concession contracts, a so-called building contracts and the  operation and transfer of ownership, The study concluded derive advantages and disadvantages of B.O.T contracts.